Polythiophene-decorated copper via polypyrrole intermediary passivation layer for enhanced electrocatalytic reduction of carbon dioxide - Venkatkarthick, Radhakrishnan; Lima, Fabio H.B. (Journal of electroanalytical chemistry (Lausanne, Switzerland), 2024)
[Display omitted] •N and S containing organic polymer-coated Cu were investigated for CO2RR using polypyrrole and polythiophene.•Polypyrrole serves for corrosion inhibition of Cu and promotes polythiophene growth by electropolymerization.•Product selectivity of C2H4 over CH4 was verified for the PTh-PPy-Cu through EC-MS analysis.•PTh-PPy-Cu exhibits enhanced FE for C2H4 compared with bare Cu at lower potentials.•PPy-Cu shows a high FE (25 %) of HCOOH formation at −1 V vs RHE in 0.1 M KHCO3. Copper is unique in catalyzing the electrochemical reduction of carbon dioxide (CO2RR) to produce C2+ hydrocarbons, but pristine Cu has a low selectivity and stability. In this study, a multilayered, N and S-containing polymer, polypyrrole (PPy), and polythiophene (PTh) were electrodeposited on polycrystalline Cu surface, and the CO2RR catalytic activity was investigated via Electrochemical Mass Spectrometry (EC-MS), Gas (GC) and Liquid (HPLC) Chromatography techniques. The PTh-PPy-Cu electrode exhibited lower CO2RR onset potential (−0.6 V vs RHE) and higher selectivity towards ethylene formation, when compared to bare Cu electrodes, as revealed by the EC-MS measurements. GC analyses also revealed that the PTh-PPy-Cu electrode exhibits higher faradaic efficiency for ethylene production than bare Cu (FE ∼ 1.4 to 7.0 %) at a relatively low overpotential (−1.0 V vs RHE). The improved selectivity of PTh-PPy-Cu for C2H4 was mainly attributed to the in-situ generated surface defects (grain boundaries), stabilized by the PTh overlayer, and to the strong hydrophobic characteristic of the polymer layer. This study could pave the way for fine-tuning the catalytic activity, selectivity, and stability of copper-containing catalysts by utilizing surface modification of metallic catalysts toward the CO2RR.